Nothing to envy : ordinary lives in North Korea - Demick, Barbara (New York : Spiegel & Grau, 2009)
Follows the lives of six North Koreans over fifteen years, a chaotic period that saw the rise to power of Kim Jong Il and the devastation of a famine that killed one-fifth of the population, illustrating what it means to live under the most repressive totalitarian regime today.
Holding hands in the dark -- Tainted blood -- The true believer -- Fade to black -- Victorian romance -- Twilight of the god -- Two beer bottles for your IV -- The accordian and the blackboard -- The good die first -- Mothers of invention -- Wandering swallows -- Sweet disorder -- Frogs in the well -- The river -- Epiphany -- The bartered bride -- Open your eyes, shut your mouth -- The promised land -- Strangers in the homeland -- Reunions -- Epilogue : Waiting.
Includes bibliographical references : pages 299-314.
Samuel Johnson Prize for non-fiction, 2010.
Keywords: Koreans -- Korea (North) -- Social conditions -- 21st century -- Case studies; Koreans -- Korea (North) -- Economic conditions -- 21st century -- Case studies; Korea (North) -- Social conditions -- 21st century; Korea (North) -- Economic conditions -- 21st century